Analisis Giro Wadi’ah dan Tabungan Wadi’ah Terhadap Laba PT BNI Syariah - Siti Nur Indah Rofiqoh; Arina Qurota Aini (JPSDa: Jurnal Perbankan Syariah Darussalam, 2021)
The research objectives of this study are: To determine the influence of wadi'ah demand deposits on PT BNI syariah earnings, to find out the amount of wadi'ah savings on PT BNI Syariah earnings and to know the simultaneous influence between wadi'ah demand deposits and wadi'ah savings on profit (Y) of PT BNI Syariah. This type of research is quantitative research. The data analysis technique used in this study is multiple linear regression. The results of this study are 1) Significantly current account (X1) to earnings (Y) is obtained tcount